GeoSiteSearch: A Tool to Map Vietnamese Diaspora by Deducing Geographical Information of Web Pages about Our Lady of LaVang - Masten, Madison G.; Ninh, Thien-Huong; Tran, Nicholas (Proceedings of the International AAAI Conference on Web and Social Media, 2020)
We construct a web tool to extract geographical locations from web pages returned by the Google search engine for an arbitrary query and display those locations on an interactive map. The tool was used to track the worldwide Vietnamese diaspora using Our Lady of LaVang as proxy for presence of a Vietnamese community, but it could potentially have other applications.